Eigenvalue sensitivity and uncertainty analysis based on a 2-D/1-D whole-core transport code KYADJ. (December 2018) - Wu, Qu; Yu, Jiankai; Shi, Guanlin; Tang, Xiao; Yu, Yingrui; Li, Qing; Wang, Kan
Highlights: Sensitivity analysis based on CPT is applied to the 2-D/1-D whole-core transport code KYADJ. 2-D MOC and 1-D Sn coupled forward-adjoint neutron transport equations are solved by an advanced iteration approach. A new covariance data file is processed from ENDF-B/VII.1 for uncertainty quantification. Abstract: An evaluated nuclear data file is one of the important footstones in reactor physics design. Nuclear data can be viewed as arguments of output parameters. Therefore, the uncertainty of nuclear data can directly influence on the uncertainty of output parameters. A process of Sensitivity and Uncertainty (S&U) analysis is used to quantify the influence. In this study, we choose 2-D/1-D transport code to develop S&U analysis in order to reduce the impact of numerical model uncertainty. We can solve 2-D/1-D adjoint transport equation and apply the classical perturbation theory to sensitivity analysis of eigenvalue with respect to nuclear data. In addition, we obtain the uncertainty of eigenvalue using the "Sandwich" rule. The Peach Bottom-2 (PB-2) BWR cell benchmark and the Three Mile Island-1 (TMI-1) PWR cell benchmark are applied to verification. The Reactor Monte Carlo code RMC is used as a reference code. The results show that the code has ability of eigenvalue sensitivity and uncertainty analysis with high accuracy.